CONDITION, TRENDS AND DEVELOPMENT FACTORS OF THE TRANSPORT STRUCTURE OF THE CITY OF CHERNIVTS - ZOLOTUNETS, Denys; KUDRINSKY, Serhii (Bulletin of Taras Shevchenko National University of Kyiv, Geography, 2025)
Background. A developed transport infrastructure is one of the defining elements of the sustainable growth of any region, because it contributes to the improvement of people's living standards, creates conditions for the effective functioning of the goods and services market, and is also a basic prerequisite for the economic growth of the country as a whole. Transport services occupy a significant place in territorial planning, because the existing and planned transport network affects the potential level of use of the territory, the location and specialization of the economy, the formation of network and logistics structures (houses, logistics centers, industrial parks, etc.). The rational use of urban space, a well-thoughtout combination of individual modes of transport (railway, road, urban, aviation, pipeline), establishing connections between communities by individual modes of transport (access roads, train stations, stations and stops, airports) creates a single transport system, the operation of which can ensure the minimization of time spent on the movement of passengers and goods, both internal and external, as well as closer and more intensive connections between communities. Transport is involved in the creation of products and the distribution of these products to consumers, it interconnects the production and consumption of products between different sectors of the economy, between countries or regions. Transport plays an important role in the emergence and development of intensive exchange of goods between the various territories involved in this division. The degree of development of transport depends on the growth of the division of labor in the territory, its strengthening and the emergence of new, more efficient forms. Transport infrastructure has an impact on the quality of life and the development of cities, therefore a deep theoretical analysis of its work becomes an important and urgent task.Methods. The following methods were used: the comparative-geographical method of the transport structure of the city of Chernivtsi, the analysis and comparison of the route network according to indicators of efficiency, resource consumption and satisfaction of passenger needs, as well as the descriptive method.Results. Using a descriptive method, negative trends in the transportation structure were identified, including the aging of vehicles, an insufficient number of routes, and the overloading of key routes. An analysis of the route network was conducted based on efficiency indicators, resource consumption, and passenger satisfaction. Based on the obtained data and analysis results, specific decisions can be made to optimize the route network, including schedule adjustments, route reorganization, and improvements in service quality and passenger satisfaction. This approach will contribute to enhancing the efficiency and effectiveness of urban public transportation.Conclusions. It was found that the transport structure of the city of Chernivtsi needs constant development and improvement, as it does not fully meet the needs of the population. Among the main tasks at the moment is the constant optimization and creation of new public transport routes to meet the needs of residents and avoid duplication between buses and electric transport. The further functioning of the city's transport system should be aimed at the maximum use of external opportunities and internal advantages, while simultaneously solving the problems of its development to ensure quality transport services in the region.
Keywords: transport structure; urban space; transport network; urban passenger transport